Tax Effort: The Impact of Corruption, Voice and Accountability - Richard M. Bird; Jorge Martinez-Vazquez; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2007)
In this paper we argue that a more legitimate and responsive state is an essential factor for a more adequate level of tax effort in developing countries. While at first glance giving such advice to poor countries seeking to increase their tax ratios may not seem more helpful than telling them to find oil, it is presumably more feasible for people to improve their governing institutions than to rearrange nature's bounty. Improving corruption, voice and accountability may not take longer nor be necessarily more difficult than changing the opportunities for tax handles and economic structure. The key contribution of this paper is to extend the conventional model of tax effort by showing that not only do supply factors matter, but that demand factors such as corruption, voice and accountability also determine tax effort to a significant extent.
Keywords: H11; H20; O17; 330; Tax effort; tax reforms; developing countries; Latin America; corruption; voice and accountability